FOREIGN INSTITUTIONAL INVESTMENT AND INDIAN STOCK MARKET – AN EMPIRICAL STUDY - E. Geetha Nambiar and H. Shankar (ISDA Journal, 2014)
According to economists foreign institutional investment flows boosts domestic stock market prices. Nevertheless the study is embarked upon to examine the relationship between FIIs and S&P BSE Sensex-proxy for the Indian stock market BSE from 2000 to 2012. The study period is further classified into two sub periods and also on yearly basis to capture the period specific impact of FII on Indian stock market. The correlation results indicate that there is significant correlation between FII and S&P BSE Sensex for all the categories of the study period, though the highest correlation was detected for the sub period II (2008-2012). As existence of correlation despite being positive does not by itself imply causality, the data were further subjected to regression analysis. The result revealed that there is linear relationship between the variables indicating that as FII inflows increases, S&P BSE Sensex mounts and this trend is manifested more during the sub period II.